The fix [videorecording (DVD)] - Egan, Kelsey; Van Dien, Grace, 1996-; Brown, Clancy; Sharman, Daniel (Gravitas Ventures, 2024)
When a troubled model takes a new drug at a party, she suffers a shocking transformation. Pursued by authorities and a dangerous gang, she hunts for a "fix" to reverse these effects, only to discover her mutations could save the human race.